Effects of bioethanol addition to the biodiesel-diesel fuel blend on diesel engine exhaust emissions - Asnawi Asnawi; Muhammad Muhammad; Abdul Rahman; Nurul Islami; Diki Dian Andika; Ihsanul Fikri Hutabarat; Irwansyah Situmorang (Politeknik Negeri Lhokseumawe, 2023)
The transition of energy sources from fossil fuel to biofuel is becoming a major topic in the world towards renewable energy to reduce greenhouse gas emissions, improve environmental air quality, and reduce dependence on fossil fuel in the future. This study aims to evaluate the effect of increasing the concentration of oxygenated biofuel in diesel fuel on the emissions of diesel engines. In this study, B30 (30% biodiesel and 70% diesel) was used as a base fuel, and a fraction of pure biodiesel (B100) was added to increase the biodiesel concentration in B30 fuel to create B40 (40% biodiesel and 60% diesel). Furthermore, the addition of 5% and 10% of bioethanol as a fuel additive in the fuel blend was conducted while maintaining a biodiesel concentration of 40%. The effect of bioethanol contained in the fuel blends was tested using a single-cylinder 418 cc diesel engine. The experiment was carried out at an engine speed of 1000–3000 rpm. The result shows that the concentration of the diesel-biodiesel-bioethanol blend affected the emissions produced by the diesel engines. Combustion efficiency increased with the concentration of biodiesel in the diesel fuel, as shown by reduced CO emissions, increased CO2 emissions, and increased NOx emissions at engine speeds of 2000–3000 rpm. In comparison to 5% bioethanol at various engine speeds, adding 10% bioethanol has a disadvantageous effect on the combustion process, increasing CO and HC emissions.